The Effect of Generational Gap and Compensation on Employee Performance Through Job Satisfaction (at CV. Citra Surya Abadi) - Aida Fuji Henarti Henarti; Sri Wahyuningsih (Sean Institute, 2025)
Improving employee performance is crucial for a company’s success as it directly impacts organizational effectiveness and efficiency. Performance is assessed based on quality, quantity, timeliness, and teamwork in achieving the company’s objectives. Job satisfaction serves as a key factor influencing individual performance and overall organizational productivity. It is affected by several factors, including the work environment, compensation system, interpersonal relationships, and career development opportunities. This study aims to analyze the effect of generational gaps and compensation on employee performance, with job satisfaction as a mediating variable. Using a quantitative survey method involving 80 respondents, the data were analyzed through instrument testing and hypothesis testing. The results indicate that generational gaps, compensation, and job satisfaction each have a positive and significant effect on employee performance. Furthermore, both generational gaps and compensation positively influence job satisfaction, and job satisfaction successfully mediates the relationship between these variables and employee performance at CV. Citra Surya Abadi.